Edward Caird - Wenley, Robert Mark (Harvard theological review, 1909)
The career of a man who devotes his life to reflection upon philosophy and religion, whose active work consists in teaching these subjects and in writing about them, is little likely to furnish incidents meet for flamboyant biography. But it may well be a source of profound influence, destined to affect the culture of a people or an age long after events that splash noisily upon the momentary surface have sunk into oblivion. Now Caird constituted an exceptional force, particularly in that native home of English-speaking philosophy and religion, Scotland; as such he merits memorial in these pages. Moreover, we must remember that, although, to his great regret, expressed to me often, he never visited the United States, his spirit has wrought strongly on this continent. Years ago, when I was a young Fellow at Glasgow, I received a letter from an American philosopher which concluded with words that have always stuck in my memory, “We look to Glasgow for light and leading.” Here Glasgow happened to be a synonym for the brothers Caird.